MONITORING OF EDUCATIONAL TECHNOLOGY PROGRESS TO ENHANCE THE QUALITY OF GRADUATE TEACHERS FROM THE KENYAN UNIVERSITIES - Mwaka, Marcella; Wambua, Benjamin Kyalo; Syomwene, Anne; Kitainge, Kisilu (European Scientific Journal, ESJ, 2013)
It makes sense for a teacher education university to keep a close watch on its environments and adapt to any changes so that it can develop contingency plans and actions which reduce the response time needed to address an environmental opportunity or threat. The close watch helps identify the needs, changes, and challenges characteristic of the environment in which the graduate teacher will work, and understand how the impact of these affects a university’s teacher preparation strategy. Accurate and timely information about critical aspects of the environment related to educational technology are crucial to the quality of graduate teachers. The purpose of this study was to establish how progress in educational technology is monitored to enhance the quality of graduate teachers from Kenyan universities. The study was guided by the General Systems Theory by Bertalanffy (1975) and adopted a descriptive survey research design. Four universities selected from ten Kenyan universities engaged in teacher preparation programs participated in the study. Data was collected from forty lecturers from the selected universities using the questionnaire. This study established that there are low interaction levels between lecturers and head teachers. The flow of information on changes in the schools to lecturers’ profession was found to be slow. The study recommends that universities develop and promote research in teacher education in order to encourage evidence-based decision-making in all aspects of teacher development. Universities also need to establish communication structures that connect all relevant stakeholders in teacher education, which will consequently enable them to identify challenges relating to use of educational technology for both students and lecturers and deal with them.